2020
DOI: 10.14341/probl12500
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and Antiandrogens influence on COVID-19 disease in men

Abstract: The WHO has declared a SARS-CoV-2 pandemic. During a pandemic, the researches aimed at finding the new treatments for SARS-CoV-2 become relevant. The review focuses on studies of androgens and antiandrogens in this disease. Since the beginning of the COVID-19 epidemic, it has been noted that men have more severe forms of infection and higher mortality. The main cause of both the severity of the disease and the high mortality of men from COVID-19 are associated with androgens. It was found that patients receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A study found that treatment with particular estrogens can decrease the severity of the disease through suppressing the expression of the protease hormone [92]. In the abovementioned theoretical basis, it is hypothesized that antiandrogen therapy in males could be effective against the viral disease [93]. Studies conducted so far have not shown any significant role of TMPRSS2 in biological processes leading to the assumption that other serine proteases might compensate for its absence [67].…”
Section: Inhibitors Of Tmprss2mentioning
confidence: 99%
“…A study found that treatment with particular estrogens can decrease the severity of the disease through suppressing the expression of the protease hormone [92]. In the abovementioned theoretical basis, it is hypothesized that antiandrogen therapy in males could be effective against the viral disease [93]. Studies conducted so far have not shown any significant role of TMPRSS2 in biological processes leading to the assumption that other serine proteases might compensate for its absence [67].…”
Section: Inhibitors Of Tmprss2mentioning
confidence: 99%